Phylogeny, biogeography, and diversification of barn owls (Aves: Strigiformes). (4th July 2016) - Aliabadian, Mansour; Alaei‐Kakhki, Niloofar; Mirshamsi, Omid; Nijman, Vincent; Roulin, Alexandre
Abstract : The existence of substantial morphological variation has resulted in the description of numerous subspecies of the cosmopolitan barn owl, Tyto alba . However, preliminary studies have revealed a high degree of genetic variation between Old and New World barn owls, suggesting that the T. alba complex may consist of several species. We present a comprehensive study of its taxonomy and propose a spatiotemporal framework to explain the origin and patterns of dispersal and diversification within these cosmopolitan owls. We used a Bayesian relaxed molecular clock approach to assess the timing of diversification. To evaluate the biogeographical pattern, we considered dispersal in addition to temporal connectivity between areas. Finally, we used ecological niche modelling to evaluate their ecological niches. Our phylogenetic analyses suggest that barn owls of the Old and New World show a high degree of genetic divergence, and the barn owls of South and South‐east Asia ( Tyto alba stertens and Tyto alba javanica ) cluster with the Australian barn owl Tyto delicatula . We propose to treat the T. alba complex as three species: T. alba (Africa, Europe), Tyto furcata (New World), and Tyto javanica (Australasia). The dating analyses indicate that the early divergence among the species of the T. alba complex took place in the Middle Miocene and we hypothesize that a common ancestor of the T. alba complex lived in Africa. A potential scenario suggests that T. alba dispersed to Europe and south‐western Asia during the interglacial periods of the Miocene/Pliocene, and dispersed into the New World either via an eastern Asian route or a western north Atlantic one.